THE IMPORTANCE OF PIRLS RESEARCH IN INCREASING THE READING LITERACY OF PRIMARY SCHOOL STUDENTS - Artikova, Nargiz (Журнал иностранных языков и лингвистики, 2022)
The role and importance of PIRLS research to improve students' reading comprehension and literacy is revealed.